Coastal engineering : waves, beaches, wave-structure interactions - Sawaragi, T. (Developments in geotechnical engineering ;, 1995)
The science and technology of coastal and ocean engineering are closely related to harbour and fishery engineering, because they share a common basic knowledge. However, whereas various publications of coastal engineering, harbour engineering, and ocean engineering have described just the knowledge in their own respective fields, an interrelated and systematic presentation linking them together has yet to be attempted. This book is the first attempt to systematically combine the fields of coastal, ocean, harbour, and fishery engineering from an engineering viewpoint backed by hydrodynamics. Understanding the interaction of waves with structures and sediment, and predicting the associated responses of interest, underlie nearly every problem in coastal and ocean engineering. This is precisely the goal of this book. Although primarily intended for use as a special textbook for graduate students and senior practising engineers, it is hoped that this book will also serve as a useful reference and assist in the further development of this field. With these objectives in mind, each chapter deals with important problems to be solved in the near future. The references included in each chapter should aid students and practising engineers in further broadening their knowledge. This book is the English translation of the original Japanese version published in May, 1991, commemorating the author's retirement from Osaka University. ``Elsevier will be named copyright holder of the English translated publication of the Work. This grant by Gihodo Publishers Ltd. (GP) only pertains to the English language version of the Work and no other rights, except to publish the Work in the English language, are granted to Elsevier Science (ES) by GP, which is acknowledged by ES to be the original copyright holder in the Work.''.